1996
DOI: 10.1016/s0272-6386(96)90256-5
|View full text |Cite
|
Sign up to set email alerts
|

Postdialysis fatigue

Abstract: To clarify the demographic and clinicolaboratory features of postdialysis fatigue (PDF), we enrolled 85 patients on maintenance hemodialysis in a cross-sectional study using validated questionnaires and chart review. Forty-three patients complained of fatigue after dialysis. On formal testing using the Kidney Disease Questionnaire, the PDF group had statistically greater severity of fatigue and somatic complaints than the group of patients without subjective fatigue (P = 0.03 and 0.04, respectively). On a scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 10 publications
6
92
0
1
Order By: Relevance
“…(21) Due to the older age of our cohort, it is possible that the prevalence of insomnia in our study was incidental to age. Studies by McCann and Boore (3) and Sklar et al (22) have reported high levels of depression among long-term haemodialysis patients, with factors such as enduring life with renal failure, long hours of haemodialysis and its complications, uncertainty about the future and financial issues being noted as the main causes of depression in these patients. Although there may have been a similar association between age and depression in our patients, this relationship was not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…(21) Due to the older age of our cohort, it is possible that the prevalence of insomnia in our study was incidental to age. Studies by McCann and Boore (3) and Sklar et al (22) have reported high levels of depression among long-term haemodialysis patients, with factors such as enduring life with renal failure, long hours of haemodialysis and its complications, uncertainty about the future and financial issues being noted as the main causes of depression in these patients. Although there may have been a similar association between age and depression in our patients, this relationship was not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…People with chronic renal disease, regardless of whether they are predialysis or receiving either HD or PD, are reported having high levels of fatigue and are often unable to engage in normal daily activities (Bonner et al, 2010). In addition, fatigue is positively correlated with depression (Chen et al, 2010;Sklar et al, 1996), and negatively correlated with QoL . In one study, researchers noted a significant relationship between the duration of treatment and the level of fatigue.…”
Section: Fatiguementioning
confidence: 99%
“…Fifteen articles met inclusion criteria (1,7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (Figure 1). Agreement beyond chance between the two authors for article inclusion was good (kappa ϭ 0.79).…”
Section: Study Selectionmentioning
confidence: 99%
“…Five were from the United States (1,13,17,24,25), one was from Canada (7), and one was from Belgium (19). The remaining three included cross-sections of patients from between 7 and 12 countries (Dialysis Outcomes and Practice Patterns Study [DOPPS] I and II) (20,21,23).…”
Section: Patterns Of Opioid Usementioning
confidence: 99%